Measurements of the B+, B0, B0 s meson and Λ0 b baryon lifetimes - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Hansmann-Menzemer, Stephanie; Jäger, Andreas; et al. (Journal of high energy physics, 2014)
Measurements of b-hadron lifetimes are reported using pp collision data, corresponding to an integrated luminosity of 1.0 fb−1, collected by the LHCb detector at a centre-of-mass energy of 7 TeV.
The LHCb collaboration: R. Aaij, B. Adeva, M. Adinolfi, A. Affolder, Z. Ajaltouni, J. Albrecht, F. Alessio, M. Alexander, S. Ali, G. Alkhazov [und 667 weitere]
Im Titel erscheinen die Zeichen + und 0 hochgestellt, die Zeichen s und b sind tiefgestellt
Im Titel wird der griechische Buchstabe Lambda verwendet
Gesehen am 19.08.2020